2009
DOI: 10.1517/14656560903168906
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pregnancy-associated breast cancer

Abstract: This article summarizes the special features of the diagnosis and primary therapy of pregnancy-associated breast cancer with particular emphasis on cytotoxic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…However, poorly differentiated, high T status, advancedstage, and metastatic breast cancers require much more complex medical treatments [1][2][3][4]. The determination of appropriate therapeutic strategies plays an important role in reducing the mortality of the disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, poorly differentiated, high T status, advancedstage, and metastatic breast cancers require much more complex medical treatments [1][2][3][4]. The determination of appropriate therapeutic strategies plays an important role in reducing the mortality of the disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide, adriamycine and fluorouracil combination is frequently used during pregnancy and is well tolerated. Anthracycline based chemotherapy can be used in pregnant women after the first trimester (62). Current evidence showed that taxanes do not pose any risk to the fetus beyond the first trimester (63).…”
Section: Systemic Chemotherapy In Pregnant Women With Breast Cancermentioning
confidence: 99%
“…Taxanes can also be appropriate for neoadjuvant chemotherapy before surgery or as a second line drug for anthracycline resistant cases. Alkylating agents and methotrexate are not used during pregnancy (62). HER2/neu is synthesized from many embryonic tissues during pregnancy.…”
Section: Systemic Chemotherapy In Pregnant Women With Breast Cancermentioning
confidence: 99%
“…For this reason, it is imperative that the pathologist be informed that the woman is pregnant or lactating. 10 After a diagnosis is made, the extent of disease is evaluated. As with non-pregnant patients with breast cancer, the TNM staging system of the American Joint Committee on Cancer is used to describe the extent of breast cancer in PABC.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…There is unresolved controversy as to whether this is due to delay in diagnosis or whether the pregnancy-associated altered vascularity, increased serum hormone levels and immunosuppression result in acceleration of tumour dynamics. 10 Oestrogen receptors and progesterone receptors are frequently negative in PABC as shown in Table 1. The high circulating concentrations of steroids in pregnancy might interfere with the assays used in determining hormonal receptor status.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%